ATM Augments Nuclear Stabilization of DYRK2 by Inhibiting MDM2 in the Apoptotic Response to DNA Damage - Taira, Naoe (American Society for Biochemistry and Molecular Biology, 2010)
The tumor suppressor p53 is a transcription factor that regulates cell cycle, DNA repair, senescence, and apoptosis in response to DNA damage. Phosphorylation of p53 at Ser-46 is indispensable for the commitment to apoptotic cell death. A previous study has shown that upon exposure to genotoxic stress, DYRK2 translocates into the nucleus and phosphorylates p53 at Ser-46, thereby inducing apoptosis. However, less is known about mechanisms responsible for intracellular control of DYRK2. Here we show the functional nuclear localization signal at N-terminal domain of DYRK2. Under normal conditions, nuclear and not cytoplasmic DYRK2 is ubiquitinated by MDM2, resulting in its constitutive degradation. In the presence of proteasome inhibitors, we detected a stable complex of DYRK2 with MDM2 at the nucleus. Upon exposure to genotoxic stress, ATM phosphorylates DYRK2 at Thr-33 and Ser-369, which enables DYRK2 to escape from degradation by dissociation from MDM2 and to induce the kinase activity toward p53 at Ser-46 in the nucleus. These findings indicate that ATM controls stability and pro-apoptotic function of DYRK2 in response to DNA damage.